2016
DOI: 10.1016/j.jastp.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Variability of mesospheric water vapor above Bern in relation to the 27-day solar rotation cycle

Abstract: a b s t r a c tMany studies investigated solar-terrestrial responses (thermal state, O 3 , OH, H 2 O) with emphasis on the tropical upper atmosphere. In this paper the focus is switched to water vapor in the mesosphere at a mid-latitudinal location. Eight years of water vapor profile measurements above Bern (°°46.88 N/7.46 E) are investigated to study oscillations with the focus on periods between 10 and 50 days. Different spectral analyses revealed prominent features in the 27-day oscillation band, which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…In Studer et al (2012) the numerical structure of the band-pass filter was shown. Lately the filter has been used to investigate the impact of the 27-day solar rotation cycle on mesospheric water vapor (Lainer et al, 2016) and to analyze the quasi 16-day planetary wave during boreal winter (Scheiben et al, 2014). We follow the advice from Oppenheim et al (1989) and run the filter with a zero phase lag forward and backward along the measurement time series.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Studer et al (2012) the numerical structure of the band-pass filter was shown. Lately the filter has been used to investigate the impact of the 27-day solar rotation cycle on mesospheric water vapor (Lainer et al, 2016) and to analyze the quasi 16-day planetary wave during boreal winter (Scheiben et al, 2014). We follow the advice from Oppenheim et al (1989) and run the filter with a zero phase lag forward and backward along the measurement time series.…”
Section: Methodsmentioning
confidence: 99%
“…In the stratosphere the vertical resolution of the water vapor profiles is 11 km and degrades to about 14 km in the mesosphere (Deuber et al, 2005). A recent validation against the Aura MLS v4.2 water vapor product (Livesey et al, 2015) revealed that for most months and altitudes the relative differences between MI-AWARA and Aura MLS are below 5 % (Lainer et al, 2016).…”
Section: Middle-atmospheric Water Vapor Radiometermentioning
confidence: 99%
“…A recent validation against the Aura MLS v4.2 water vapor product revealed that for most months and altitudes the relative differences between MIAWARA and Aura MLS are below 5 % (Lainer et al, 2016 MIAWARA water vapor data set used during this study has a temporal resolution of 6 h. This is useful to study not only the Q2DW but also possible interactions with waves of shorter periods like tides. Compared to an even higher temporally resolved H 2 O data set like the one used in Lainer et al (2017) with a 3 h time interval, the 6 h interval ensures usability also during summer when the measurement sensitivity is lower.…”
Section: Data From Ground-based Water Vapor Radiometrymentioning
confidence: 95%
“…9a the highest wavelet power (label A) is found at coordinates (48, > 64) and could be related to an interference of the Q2DW with the quasi 18 h wave, which itself is likely to originate from a nonlinear wave-wave coupling between the diurnal tide and the westward-traveling quasi 2-day wave (W2) (Lieberman et al, 2017). A recent study by Lainer et al (2016) revealed dominant oscillations in mesospheric water vapor profiles with a period close to 18 h in Northern Hemispheric winter months. However, such oscillations within a sub-diurnal period spectrum in the MLT can also be related to low-frequency inertia-gravity waves, as shown by Li et al (2007) with measurements from a sodium lidar system over Fort Collins, Colorado (41 • N, 105 • W).…”
Section: Autobicoherence Analysismentioning
confidence: 96%
See 1 more Smart Citation